2013
DOI: 10.1108/ijm-04-2013-0078
|View full text |Cite
|
Sign up to set email alerts
|

Weathering the storm? Multinational companies and human resource management through the global financial crisis

Abstract: Purpose -This paper aims to examine the impact of the global financial crisis on human resource management (HRM) in multinational companies (MNCs) in Ireland. It focuses on four key areas of HR, namely staffing, pay and benefits, industrial relations and the HR function. Design/methodology/approach -It uses a mixed methods approach involving four major data sources combining objective information reported on the impact of the GFC on HRM with subjective perspectives on HRM practice within MNCs. Findings -Specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 22 publications
3
45
0
Order By: Relevance
“…For example, in response to security risks, some MNCs have revised their policies and practices related to employees' use of international assignments and travel. Research by Gunnigle et al (2013) found that, in MNCs responding to the global financial crisis that began in 2008, the HRM function plays an important role in organisational change and re-structuring, downsizing, working time reductions, industrial relations negotiations and related changes in reward systems and working conditions. While some of these MNC activities in crisis management might encompass work-life management, there appears to have been little specific analysis of the implications of changes in worklife policies and practices in response to external shocks.…”
Section: External Influencesmentioning
confidence: 99%
“…For example, in response to security risks, some MNCs have revised their policies and practices related to employees' use of international assignments and travel. Research by Gunnigle et al (2013) found that, in MNCs responding to the global financial crisis that began in 2008, the HRM function plays an important role in organisational change and re-structuring, downsizing, working time reductions, industrial relations negotiations and related changes in reward systems and working conditions. While some of these MNC activities in crisis management might encompass work-life management, there appears to have been little specific analysis of the implications of changes in worklife policies and practices in response to external shocks.…”
Section: External Influencesmentioning
confidence: 99%
“…However, at the same time, uncertainty and resultant austerity provokes ambiguity, complexity, and information overload (Carpenter & Fredrickson, 2002). In this situation, undoubtedly, management choices may become erratic, and this is habitually reflected in decisions that impact investment in employee capabilities (Gunnigle et al, 2013;McCarthy & Sheehan, 2014).…”
Section: Temporary Workersmentioning
confidence: 99%
“…resource (HR) expenditure is usually the first to be scrutinised and cut back (Bloom, 2014;Gunnigle, Lavelle, & Monaghan, 2013).…”
mentioning
confidence: 99%
“…To overcome the effects of the financial crisis, multinational enterprises (MNEs) located in Ireland have also restructured their HR practices. In parallel, the drop in unit labor costs has helped the Irish economy to restore investors’ belief and reverse the trend of FDI by attracting substantial investments (Gunnigle, Lavelle, & Monaghan, ). Despite the initial drop in 2007, FDI projects peaked in 2011, with a total of 16,000 jobs and US$7.06 billion in capital invested (Aliouche, ; fDi Markets, ).…”
Section: Introductionmentioning
confidence: 99%